Effect of fermented wild plant leaf extract on crop growth and productivity of Tomato (Lycopersicon esculentum L)” - Kalpana Palghadmal (The Bioscan, 2025)
Twelve different wild plant leaves were collected ie Azadirachta indica,Annona squamosa Gnidia glauca (Fres.) Gilg,Ricinus communis , Cascabela thevetia,Clitoria ternatea, Ailanthus excels ,Parthenium hysterophorus, Calotropis procera,Vachellia leucophloea,Gelshendi were selected and all collected plant Leaves soaked in 250 liters of water and 25 to 30 liters of cow urine was added along with 10 gm dried tobacco leaves were added to prevent insects as well as 2 to 3 kg of lime was added then all the mixture kept for fermentation for 2 months and after 15 days of time interval the spraying of formulation was given with seven different concentrations (10%, 20%, 40%, 60%, 80% and , 100% ) including control. In this present investigation it was found that highest Average plant height (78.9cm) was recorded in theT4 (40% conc.),Average number of branches(24.3) , Average number of Leaves(197.6), Average number of flower bud (10.3), Average number of fruits(19) and Average number of fruits(483.3)followed by T5 (60% conc.) Average plant height (77.9) , Average number of branches(22.6), Average number of Leaves(185.6) Average number of flower bud (11) , Average weight of fruits( 16.3 gm.) and Average number of fruits(413gm)